First-Principles Study on the Interaction of H2O and Interface Defects in A-SiO2/Si(100) - Zhang, Wenli; Zhang, Jinli; Liu, Yang; Zhu, Haoran; Yao, Pei; Liu, Xin; Liu, Xuehua; Zuo, Xu (Frontiers in Materials, 2022)
The defects contained in amorphous SiO2/Si (a-SiO2/Si) interface have a considerable impact on the efficiency and stability of the device. Since the device is exposed to the atmospheric environmental conditions chronically, its performance will be limited by water diffusion and penetration. Here, we simulated the interaction of H2O and interface defects in a-SiO2/Si(100) by using the first-principles method. Our results suggest that H2O penetrated into Pb0 defect is more inclined to interact with the network in the form of silanol (Si-OH) group, while H2O incorporated into Pb1 defect is more likely to remain intact, which can be attributed to the location of Pb1 defect closer to the interface than that of Pb0 defect. Our research provides a powerful theoretical guidance for the interaction of H2O and interface defects in a-SiO2/Si(100).